Loss of p27kip1 increases genomic instability and induces radio-resistance in luminal breast cancer cells - Stefania Berton (Nature Portfolio, 2017)
Abstract Genomic instability represents a typical feature of aggressive cancers. Normal cells have evolved intricate responses to preserve genomic integrity in response to stress, such as DNA damage induced by γ-irradiation. Cyclin-dependent kinases (CDKs) take crucial part to these safeguard mechanisms, but involvement of CDK-inhibitors, such as p27Kip1, is less clear. We generated immortalized fibroblasts from p27kip1 knock-out (KO) mouse embryos and re-expressed p27kip1 WT, or its mutant forms, to identify the function of different domains. We γ-irradiated fibroblasts and observed that loss of p27Kip1 was associated to accumulation of residual DNA damage, increased number of mitotic aberration and, eventually, to survival advantage. Nuclear localization and cyclin/CDK-binding of p27Kip1 were critical to mediate proper response to DNA damage. In human luminal breast cancer (LBC) p27kip1 is frequently down-modulated and CDKN1B, p27Kip1 gene, sporadically mutated. We recapitulated results obtained in mouse fibroblasts in a LBC cell line genetically manipulated to be KO for CDKN1B gene. Following γ-irradiation, we confirmed that p27kip1 expression was necessary to preserve genomic integrity and to recognize and clear-out aberrant cells. Our study provides important insights into mechanisms underlying radio-resistance and unveils the possibility for novel treatment options exploiting DNA repair defects in LBC.